Investigating the (Mis)alignment between Expenditures and Policy to Improve Multilingual Learner Programs - Correia, Amy; Hos, Rabia; Cahan, James (Journal of Educational Leadership and Policy Studies, 2024)
States and districts share an obligation to provide Multilingual Learners (MLLs) with access to high quality language programs that are proven to be effective in minimizing opportunity gaps between MLLs and non-MLLs. This article reviews how local education agencies (LEAs) allocated their state-issued funding to improve MLL language programs and increase student outcomes. Findings reveal that of the total state-issued MLL funding, LEAs used 88.7% on teacher salaries and benefits, 5.1% on teacher professional development, 4.9% on language program implementation, 0% on language program evaluation, and a small percentage of funding remained unspecified. Collectively, these findings indicate that LEAs did not adhere to the state's funding policies, nor did the state follow their own policies to regulate the LEAs' expenditures. We close with a discussion on how the state can improve their function as an organizational leader and serve as a model for other stakeholders in the shared obligation of the education of MLLs.
Keywords: Elementary Secondary Education; English (Second Language); English Language Learners; Expenditures; Financial Support; Fringe Benefits; Multilingualism; Outcomes of Education; Policy Analysis; Program Implementation; Program Improvement; Resource Allocation; School Districts; Second Language Learning; Second Language Programs; State Policy; Teacher Salaries; dept.grad